Probiotics and inflammatory bowel disease: an umbrella meta-analysis of relapse, recurrence, and remission outcomes. - Liu, Wei; Zhang, Shengbo; Dong, Changzheng; Lv, Xia; Zheng, Ximin; Zhao, Wei; Jamali, Mehrdad; Abedi, Ranasadat; Saedisomeolia, Ahmad (Nutrition & Metabolism, 2025)
Background: Inflammatory Bowel Diseases (IBD) encompass chronic inflammatory conditions such as ulcerative colitis and Crohn's disease. This umbrella meta-analysis investigates the efficacy of probiotic supplementation in reducing relapse, recurrence, and maintaining remission in IBD patients. Methods: We systematically searched PubMed, Scopus, and Web of Science up to November 2024 for meta-analyses evaluating probiotics in IBD. A random-effects model calculated pooled effect sizes. The methodological quality of included reviews was assessed using AMSTAR 2. Publication bias was evaluated through funnel plots, Egger's and Begg's tests, and corrected by trim-and-fill when appropriate. Results: Twenty meta-analyses including 46 datasets were analyzed. Probiotics significantly reduced relapse risk compared to placebo (RR = 0.55; 95% CI, 0.22–0.88), but showed no significant effect compared to mesalazine. No consistent benefit was found for remission or recurrence; however, recurrence risk was reduced after correction for publication bias (RR:0.74;95%CI:0.51–0.97, P < 0.05). Subgroup analyses suggested greater benefit with lower probiotic doses (≤ 10¹⁰ Colony-Forming Units/day) and longer supplementation durations (≥ 8 weeks) regarding to relapse rate, although strain-specific effects could not be clarified. Conclusion: Probiotic supplementation appears effective in reducing relapse compared to placebo, but shows no advantage over mesalazine and demonstrates benefit for recurrence only after adjusting for publication bias. These findings highlight a potential role for probiotics in IBD management, but interpretation should be cautious given the high heterogeneity and substantial overlap among included meta-analyses. Further high-quality, non-overlapping meta-analyses and randomized controlled trials are needed to determine the most effective probiotic regimens.